The Social Responsiveness Scale (SRS-2) in school-age children with Down syndrome at low risk for autism spectrum disorder. (October 2020) - Channell, Marie Moore
Background and aims: Little is known about how autism spectrum disorder (ASD) symptoms present in individuals with Down syndrome (DS). Some behaviors may be symptomatic of comorbid ASD or more broadly representative of the DS phenotype. A prior research study documented elevated ASD-like symptoms in adolescents and young adults with DS without comorbid ASD, using a common ASD risk screening tool—the Social Responsiveness Scale (SRS). The current study applied a similar approach to younger children with DS using the SRS-2. The primary aim was to document patterns of ASD-like symptoms in children with DS at low risk of comorbid ASD to distinguish the symptoms that may be present across DS in general. Methods: SRS-2 standard scores were analyzed in a sample of 40 children with DS, 6–11 years old, who were considered to be at low risk for ASD based on the Social Communication Questionnaire (SCQ) screener. Other developmental characteristics (i.e., age, nonverbal IQ, expressive language), social skills, and problem behaviors were also examined across the sample. Results: SRS-2 scores were significantly elevated in this sample compared to the normative population sample. A pattern of ASD-like symptomatology was observed across SRS-2 subdomains. These findings were similar to the findings of the prior study. However, nuanced differences were observed across the two samples that may represent developmental differences across different ages in this population. Conclusions: Replicating and extending a prior study's findings, certain ASD-like behaviors may occur in individuals with DS who are at low risk for comorbid ASD. Implications: Understanding the pattern of ASD-like behaviors that occur in children with DS who are at low risk for comorbid ASD will help clinicians in screening and identification efforts. In particular, it will lead to better specification of the behaviors or symptoms that are not characteristic of the DS phenotype and thus are red flags for comorbid ASD in this population.